2009
DOI: 10.1098/rsif.2009.0284
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the impact of waiting time distributions on the persistence of measles

Abstract: Measles epidemics in human populations exhibit what is perhaps the best empirically characterized, and certainly the most studied, stochastic persistence threshold in population biology. A critical community size (CCS) of around 250 000 -500 000 separates populations where measles is predominantly persistent from smaller communities where there are frequent extinctions of measles between major epidemics. The fundamental mechanisms contributing to this pattern of persistence, which are long-lasting immunity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 71 publications
(191 reference statements)
0
61
0
Order By: Relevance
“…We find that reporting probabilities vary greatly between disease, geographical region and metapopulation. This variability directly affects patterns of observed extinctions or 'fade-outs' [2,11,38] and, if not addressed, makes comparisons between diseases and metapopulations difficult.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We find that reporting probabilities vary greatly between disease, geographical region and metapopulation. This variability directly affects patterns of observed extinctions or 'fade-outs' [2,11,38] and, if not addressed, makes comparisons between diseases and metapopulations difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Several works have explicitly incorporated estimation of incomplete and variable reporting into dynamical models of populations [6,17] and metapopulations [7]. Nonetheless, disease reporting (and variability thereof ) has been largely absent from modern population and metapopulation models that studied stochastic extinction and disease persistence in E&W [11,[24][25][26]. These models (and results) do not necessarily generalize to metapopulations with lower and more variable reporting, such as the pre-vaccine US or modern sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been considerable debate in recent years concerning the most appropriate formulation of the SIR model for childhood infections such as measles [20][21][22][23][24][25][26]. We follow Krylova & Earn [6,27], who showed that for measles, the simplest sinusoidally forced SIR model-when suitably parametrized-makes identical predictions to more complicated versions of the model that include realistically distributed latent and infectious periods (details in §3.1).…”
Section: Introductionmentioning
confidence: 99%